Negative electrode active material and method for producing the same

The development of a negative electrode active material with amorphous low-valent nanosilicon oxide dispersed in porous carbon addresses the challenges of silicon-based lithium-ion batteries, improving capacity, cycle characteristics, and fast rechargeability.

JP2025066565APending Publication Date: 2025-04-23SHIN ETSU CHEMICAL CO LTD
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2023176260
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-23

AI Technical Summary

Technical Problem

Current lithium-ion secondary batteries using silicon as the negative electrode active material face challenges such as expansion and cracking during charging and discharging, leading to reduced cycle characteristics and fast rechargeability.

Method used

A negative electrode active material is developed, comprising a structure of porous carbon with amorphous low-valent nanosilicon oxide dispersed inside. This material includes SiOx states where x<1.0, with an average particle diameter of 50 nm or less, and is produced using a method that involves depositing silicon inside the porous carbon structure and converting it into low-valent nanosilicon oxide using diluted oxygen.

Benefits of technology

The proposed negative electrode active material enhances battery capacity while maintaining good cycle characteristics and fast rechargeability, by reducing irreversible capacity and suppressing electrolyte decomposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066565000001_ABST
    Figure 2025066565000001_ABST
Patent Text Reader

Abstract

To provide a negative electrode active material which is capable of increasing the capacity while maintaining the battery characteristics.SOLUTION: There is provided a negative electrode active material including negative electrode active material particles. The negative electrode active material particles each include a porous carbon structure. An amorphous low-valence nano silicon oxide is dispersed inside the porous carbon structure. The low-valence nano silicon oxide includes states where SiOx: x<1.0 is satisfied, and has an average particle diameter of 50 nm or less, the average particle diameter being determined by image processing of a cross-sectional TEM image thereof.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode active material and a method for producing the same. [Background technology]

[0002] In recent years, small electronic devices such as mobile terminals have become widespread, and there is a strong demand for further miniaturization, weight reduction, and longer life. In response to such market demands, development of secondary batteries that are small, lightweight, and capable of obtaining high energy density has been promoted. The application of these secondary batteries is being considered not only for small electronic devices, but also for large electronic devices such as automobiles and power storage systems such as homes.

[0003] Among these, lithium-ion secondary batteries are attracting great attention because they can be easily made small and have a high capacity, and because they offer a higher energy density than lead-acid batteries and nickel-cadmium batteries.

[0004] The lithium ion secondary battery includes a positive electrode, a negative electrode, a separator, and an electrolyte solution, and the negative electrode contains a negative electrode active material involved in charge and discharge reactions.

[0005] While carbon-based active materials are widely used as negative electrode active materials, recent market demands have called for further improvements in battery capacity. To improve battery capacity, the use of silicon as a negative electrode active material is being considered. This is because the theoretical capacity of silicon (4199mAh / g) is more than 10 times greater than that of graphite (372mAh / g), and a significant improvement in battery capacity can be expected. In the development of silicon materials as negative electrode active materials, not only silicon itself but also alloys and compounds such as oxides are being considered. In addition, the active material shape is being considered, ranging from the standard coating type for carbon-based active materials to an integrated type that is directly deposited on the current collector.

[0006] However, when silicon is used as the main raw material for the negative electrode active material, the negative electrode active material expands and contracts during charging and discharging, making it prone to cracking, mainly near the surface layer of the negative electrode active material. In addition, ionic substances are generated inside the active material, making the negative electrode active material prone to cracking. When the surface layer of the negative electrode active material cracks, a new surface is formed, and the reaction area of ​​the active material increases. At this time, a decomposition reaction of the electrolyte occurs on the new surface, and a coating, which is a decomposition product of the electrolyte, is formed on the new surface, consuming the electrolyte. This makes the cycle characteristics prone to deterioration.

[0007] To date, various studies have been conducted on negative electrode active materials and electrode configurations for lithium-ion secondary batteries that are primarily made of silicon materials in order to improve the initial battery efficiency and cycle characteristics.

[0008] Specifically, in order to obtain good cycle characteristics and high safety, silicon and amorphous silicon dioxide are simultaneously deposited using a gas phase method (see, for example, Patent Document 1). Also, in order to obtain high battery capacity and safety, a carbon material (electron conductive material) is provided on the surface layer of silicon oxide particles (see, for example, Patent Document 2). Furthermore, in order to improve cycle characteristics and obtain high input / output characteristics, an active material containing silicon and oxygen is prepared, and an active material layer with a high oxygen ratio is formed near the current collector (see, for example, Patent Document 3). Also, in order to improve cycle characteristics, oxygen is contained in the silicon active material, and the active material is formed so that the average oxygen content is 40 at% or less and the oxygen content is high in the area close to the current collector (see, for example, Patent Document 4).

[0009] In addition, in order to improve the initial charge / discharge efficiency, the Si phase and SiO 2 , M y Nanocomposites containing metal oxides are used (see, for example, Patent Document 5). In addition, in order to improve cycle characteristics, SiO x(0.8 ≦ x ≦ 1.5, particle size range = 1 μm to 50 μm) is mixed with a carbon material and fired at high temperature (see, for example, Patent Document 6). Further, in order to improve cycle characteristics, the molar ratio of oxygen to silicon in the negative electrode active material is set to 0.1 to 1.2, and the active material is controlled within a range where the difference between the maximum value and the minimum value of the molar ratio near the active material and current collector interface is 0.4 or less (see, for example, Patent Document 7). Further, in order to improve the battery load characteristics, a metal oxide containing lithium is used (see, for example, Patent Document 8). Further, in order to improve cycle characteristics, a hydrophobic layer such as a silane compound is formed on the surface layer of the silicon material (see, for example, Patent Document 9).

[0010] Also, in order to improve cycle characteristics, silicon oxide is used, and conductivity is imparted by forming a graphite film on its surface layer (see, for example, Patent Document 10). In Patent Document 10, regarding the shift value obtained from the Raman spectrum of the graphite film, broad peaks appear at 1330 cm -1 and 1580 cm -1 , and the intensity ratio I 1330 / I 1580 is such that 1.5 < I 1330 / I 1580 < 3. Also, in order to improve high battery capacity and cycle characteristics, particles having a silicon microcrystalline phase dispersed in silicon dioxide are used (see, for example, Patent Document 11). Further, in order to improve overcharge and overdischarge characteristics, a silicon oxide in which the atomic ratio of silicon to oxygen is controlled to 1:y (0 < y < 2) is used (see, for example, Patent Document 12).

[0011] Also, Hitachi Maxell started shipping a rectangular secondary battery for smartphones that adopted a nanosilicon composite in June 2010 for a lithium ion secondary battery using silicon oxide (see, for example, Non-Patent Document 1). The silicon oxide proposed by Hohl is a composite material of Si 0+ ~Si 4+ and has various oxidation states (Non-Patent Document 2). Also, Kapaklis proposed a disproportionation structure that is divided into Si and SiO2 by applying a heat load to the silicon oxide (Non-Patent Document 3).

[0012] Miyachi et al. have reported that the Si and SiO oxides that contribute to charging and discharging among the silicon oxides with disproportionated structures are 2 (Non-Patent Document 4), and Yamada et al. have proposed the following reaction formula between silicon oxide and Li (Non-Patent Document 5): 2SiO(Si+SiO 2 ) + 6.85Li + + 6.85e - → 1.4Li 3.75 Si + 0.4Li 4 SiO 4 + 0.2SiO 2 In the reaction formula, silicon oxide consists of Si and SiO 2 reacts with Li to produce Li silicide, Li silicate, and some unreacted SiO 2 Divided into two.

[0013] The Li silicate formed here is irreversible, and it is generally said to be a stable substance that does not release Li once it is formed. The capacity per mass calculated from this reaction formula is close to the experimental value, and is recognized as the reaction mechanism of silicon oxide. Kim et al. have reported that the irreversible component Li silicate that accompanies the charge and discharge of silicon oxide is Li 4 SiO 4 As, 7 Li-MAS-NMR and 29 The identification was carried out using Si-MAS-NMR (Non-Patent Document 6).

[0014] This irreversible capacity is the weakest point of silicon oxide, and there is a need to improve it. Kim et al. have used a Li pre-doping method to form Li silicate in advance, significantly improving the initial efficiency of the battery and producing a negative electrode that can withstand practical use (Non-Patent Document 7). They also proposed a method of treating the powder rather than a method of doping the electrode with Li, and have achieved an improvement in the irreversible capacity (Patent Document 13).

[0015] On the other hand, the price of Li metal used for Li doping is subject to large fluctuations depending on the market situation, and there are many issues when viewed as industrialization. Therefore, CVD-Si-C, which uses silane gas in porous carbon to generate nanosilicon inside, has achieved a higher energy density than Li-doped SiO (Patent Documents 14 and 15). [Prior art documents] [Patent documents]

[0016] [Patent Document 1] JP 2001-185127 A [Patent Document 2] JP 2002-042806 A [Patent Document 3] JP 2006-164954 A [Patent Document 4] JP 2006-114454 A [Patent Document 5] JP 2009-070825 A [Patent Document 6] JP 2008-282819 A [Patent Document 7] JP 2008-251369 A [Patent Document 8] JP 2008-177346 A [Patent Document 9] JP 2007-234255 A [Patent Document 10] JP 2009-212074 A [Patent Document 11] JP 2009-205950 A [Patent Document 12] Japanese Patent Application Publication No. 06-325765 [Patent Document 13] JP 2015-156355 A [Patent Document 14] U.S. Pat. No. 10,608,254 [Patent Document 15] U.S. Patent No. 11,165,054

Non-Patent Document

[0017]

Non-Patent Document 1

Non-Patent Document 2

Non-Patent Document 3

Non-Patent Document 4

Non-Patent Document 5

Non-Patent Document 6

Non-Patent Document 7

[0018] As mentioned above, in recent years, small electronic devices such as mobile terminals have become more powerful and multifunctional, and there is a demand for increased battery capacity for the lithium-ion secondary batteries that serve as their main power sources. As one method for solving this problem, there is a demand for the development of lithium-ion secondary batteries with a negative electrode that uses silicon material as the main material.

[0019] In addition, lithium ion secondary batteries using silicon materials are expected to have initial charge / discharge characteristics and cycle characteristics that are close to those of lithium ion secondary batteries using carbon-based active materials. Therefore, by using silicon oxide modified by insertion and partial desorption of Li as the negative electrode active material, cycle characteristics and initial charge / discharge characteristics have been improved. Recently, silicon oxide is mainly used, Li is contained in advance, and Li silicate is generated, which reduces the irreversible capacity, which is a disadvantage of silicon oxide, and has actually begun to be put on the market. Even if a battery is prototyped by replacing 100% of Li-SiO-C (Non-Patent Document 8), which uses Li in this silicon oxide, with carbon negative electrode material, the capacity improvement is only in the late 20% range compared to carbon negative electrode material. This means that further improvement in battery capacity is required when considering the high performance of small electronic devices (5G, etc.) and the improvement of the driving distance of electric vehicles.

[0020] Therefore, CVD-Si-C, which has a low irreversible capacity, was developed, but it is known that the reaction between Si and the electrolyte results in insufficient high-speed charging and battery cycle characteristics.

[0021] The present invention has been made in consideration of the above problems, and has an object to provide a negative electrode active material that can increase the capacity while maintaining the battery characteristics. [Means for solving the problem]

[0022] In order to solve the above problems, the present invention provides a negative electrode active material having negative electrode active material particles, the negative electrode active material particles including a porous carbon structure, amorphous low-valence nanosilicon oxide being dispersed inside the porous carbon structure, the low-valence nanosilicon oxide including each state of SiOx:x<1.0, and the low-valence nanosilicon oxide having an average particle size of 50 nm or less as determined by image processing of a cross-sectional TEM image.

[0023] The negative electrode active material of the present invention has amorphous low-valence nano-silicon oxide dispersed inside the porous carbon structure, so that the presence of the porous carbon structure can reduce the adverse effect of the expansion of the low-valence nano-silicon oxide inside. 4+ However, in the negative electrode active material of the present invention, since it contains each state of SiOx:x<1.0, it is possible to maintain a lower irreversible capacity than general SiO. In addition, since the Si-O bond can suppress the decomposition of the electrolyte, it is possible to reduce the SEI (Solid Electrolyte Interphase) that accumulates in the surface layer. In addition, since the particle size of the low-valence nanosilicon oxide (particle size obtained by image processing of a cross-sectional TEM image of the low-valence nanosilicon oxide) is an average of 50 nm or less, it is easy to form the Si-O bond appropriately.

[0024] In this case, the low valence nano silicon oxide is preferably substantially in a composite state of zero valence, monovalence and divalence.

[0025] In this way, the low-valent nano silicon oxide is substantially in a composite state of zero valence, monovalence and divalence, and therefore, can have a lower irreversible capacity.

[0026] The negative electrode active material particles are solid 29 It is preferable that, when measured by Si-MAS-NMR, no hydrogen is detected in the vicinity of the low valence nano silicon oxide.

[0027] Thus, solid 29 If the negative electrode active material particles are such that no hydrogen is detected in the vicinity of the low valence nano silicon oxide when measured by Si-MAS-NMR, the irreversible capacity can be further reduced.

[0028] Furthermore, the low valence nano silicon oxide dispersed in the porous carbon structure may have x increasing from the center to the surface layer of the porous carbon structure.

[0029] In this way, in the present invention, since low-valence nanosilicon oxide is dispersed in the porous carbon structure, x tends to increase (the composition ratio of oxygen becomes larger) from the center of the porous carbon structure to the surface during production. Since the oxidation ratio of silicon is large at the surface, decomposition of the electrolyte is more effectively suppressed, while the oxidation ratio of silicon is small inside the active material, so the battery capacity can be increased.

[0030] The porous carbon structure preferably has carbon-carbon double bonds at least in a part thereof.

[0031] In this way, since the porous carbon structure has carbon-carbon double bonds, the structure can be made rigid and flexible, and the adverse effects of the expansion of the low-valence nanosilicon oxide inside can be more effectively reduced.

[0032] The proportion of the porous carbon structure in the entire negative electrode active material particles is preferably 38 mass % or more and 63 mass % or less.

[0033] With such a ratio, it is possible to effectively achieve both ensuring the battery capacity and mitigating the volume change of the low-valence nanosilicon oxide due to the porous carbon structure.

[0034] The low valence nano silicon oxide is a solid 29 In Si-MAS-NMR measurement, it is preferable that the compound has a broad peak with a top at about −87 ppm.

[0035] If such a peak is present, it can be more reliably determined that the material contains SiOx:x<1.0.

[0036] In addition, the grain size of zero-valent Si constituting the low-valent nanosilicon oxide, calculated using the Scherrer formula from the peak measured by X-ray diffraction measurement of the negative electrode active material particles, is preferably in the range of 1 nm to 5 nm.

[0037] Such a grain size of zero-valent Si that is substantially amorphous is preferable.

[0038] The negative electrode active material particles preferably have a G / D ratio, as determined by Raman spectroscopy, in the range of 0.85 to 1.15, and a Si / G ratio of 0.25 or more and 0.5 or less.

[0039] If the G / D ratio is within the above range, the material is neither too hard nor too soft. If the ratio is within the above range, it is possible to prevent cracking during pressing or cracking due to volume change during Li absorption by low-valence nanosilicon. Also, if the Si / G ratio is within the above range, the area of ​​the low-valence nanosilicon oxide part visible on the particle surface is more appropriate. If the ratio is within the above range, it is possible to ensure high-speed charging while suppressing deterioration.

[0040] The porous carbon structure is predominantly type I in the IUPAC classification, and its surface area is 1400 m 2 / g or more, pore volume is 1cm 3 It is preferable that the molecular weight is 1 / g or more.

[0041] The porous carbon structure has the above IUPAC classification, surface area, and pore volume, making it possible to produce a negative electrode active material that efficiently contains a large amount of low-valence nanosilicon oxide. In particular, the IUPAC type I structure allows smooth Si-O bond formation after deposition.

[0042] The present invention also provides a method for producing a negative electrode active material having negative electrode active material particles, the method comprising the steps of: preparing a porous carbon structure; depositing silicon inside the porous carbon structure by flowing monosilane gas through the porous carbon structure under heating; cooling the material with silicon deposited inside the porous carbon structure to 50°C or less; and, after the cooling, adjusting the temperature of the material with silicon deposited inside the porous carbon structure to be maintained at 50°C or less, introducing oxygen diluted with nitrogen gas into the material with silicon deposited inside the porous carbon structure to convert at least a portion of the silicon into low-valence nanosilicon oxide, thereby producing negative electrode active material particles in which amorphous low-valence nanosilicon oxide is dispersed inside the porous carbon structure.

[0043] Such a method for producing a negative electrode active material can simply and efficiently produce a negative electrode active material in which amorphous low-valent nanosilicon oxide is dispersed inside a porous carbon structure, as described above. Effect of the Invention

[0044] The negative electrode active material of the present invention is a material in which amorphous low-valence nanosilicon oxide is dispersed inside the porous carbon structure, and therefore, when the low-valence nanosilicon oxide inside expands due to the presence of the porous carbon structure, the adverse effects of the expansion can be reduced. Since it includes each state of SiOx:x<1.0, it is possible to maintain a lower irreversible capacity than general SiO. In addition, since the Si-O bond can suppress the decomposition of the electrolyte, it is possible to reduce the SEI deposited on the surface layer. In addition, since the particle size of the low-valence nanosilicon oxide (particle size obtained by image processing of a cross-sectional TEM image of the low-valence nanosilicon oxide) is an average of 50 nm or less, it is easy to form an Si-O bond appropriately. As a result, the negative electrode using the negative electrode active material of the present invention can obtain high initial efficiency, high capacity, high input characteristics, and high cycle characteristics.

[0045] Furthermore, the method for producing a negative electrode active material of the present invention can simply and efficiently produce a negative electrode active material in which amorphous low-valent nanosilicon oxide is dispersed inside the porous carbon structure. [Brief description of the drawings]

[0046] [Figure 1] 1 is a cross-sectional view showing the configuration of a negative electrode containing a negative electrode active material of the present invention. [Diagram 2] FIG. 1 is an exploded view showing a configuration example (laminate film type) of a lithium ion secondary battery including the negative electrode active material of the present invention. [Diagram 3] 1 is a cross-sectional TEM photograph of an example of a negative electrode active material of the present invention. [Figure 4] FIG. 2 is a flow chart showing an example of a method for producing a negative electrode active material according to the present invention. [Diagram 5] 1 shows the results of solid-state 29Si-MAS-NMR measurement of the negative electrode active material in Example 1 and each control example. [Figure 6] 1 is a graph showing changes in the O1s region in the depth direction measured in an XPS measurement of the negative electrode active material in Example 1. [Figure 7]1 is a graph showing the results of the Si2p region in XPS measurements of the negative electrode active materials in Example 1, Comparative Example 1, and Comparative Example 3. [Figure 8] 2 shows a 29Si-MAS-NMR spectrum and a 29Si-CP / MAS-NMR spectrum of an example of the negative electrode active material of the present invention. [Figure 9] 13C-MAS-NMR spectra of Example 1 and a control example. [Figure 10] 1 shows the results of TEM-EDX measurement of the negative electrode active material of Example 1, in which the upper figure is a cross-sectional TEM photograph showing the measurement points, and the lower figure is a graph showing the relationship between the distance from the surface and the mass % of elements. [Figure 11] 1 shows X-ray diffraction spectra of Examples 1, 2, 15, and 16. [Figure 12] 1 is a graph showing charge / discharge characteristics of Example 1, Comparative Example 1, and Example 11. [Figure 13] FIG. 13 is a partially enlarged view of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0047] Hereinafter, the present invention will be described in detail with reference to the preferred embodiments, but the present invention is not limited thereto.

[0048] As mentioned above, one method to increase the battery capacity of lithium-ion secondary batteries is to use a negative electrode that uses low-valence nanosilicon oxide as the main material in the carbon structure. Lithium-ion secondary batteries using this active material are expected to have high battery capacity while exhibiting battery characteristics similar to those of lithium-ion secondary batteries using carbon-based active materials.

[0049] Therefore, the inventors have conducted extensive research in order to obtain a negative electrode active material that can improve initial charge / discharge characteristics and increase battery capacity while obtaining high cycle characteristics when used as a negative electrode of a secondary battery, and have arrived at the present invention.

[0050] In particular, the CVD-Si-C disclosed in Patent Documents 14 and 15 has an issue of excessive reaction with the electrolyte. In the present invention, in order to suppress such a reaction with the electrolyte, the Si portion is converted to a Si-O phase and the siloxane bond specific to silicon oxide is used, thereby developing a negative electrode active material that not only significantly suppresses the reactive decomposition of the electrolyte, but also ensures high-speed charging because the Si-O material with siloxane bond has good Li acceptance.

[0051] [Negative electrode active material of the present invention] The negative electrode active material of the present invention is a negative electrode active material having negative electrode active material particles, the negative electrode active material particles including a porous carbon structure, amorphous low-valence nanosilicon oxide being dispersed inside the porous carbon structure, the low-valence nanosilicon oxide including each state of SiOx:x<1.0, and the low-valence nanosilicon oxide having an average particle size of 50 nm or less as determined by image processing of a cross-sectional TEM image.

[0052] Since such an anode active material has amorphous low-valence nanosilicon oxide dispersed inside the porous carbon structure, the presence of the porous carbon structure can reduce the adverse effect of the expansion of the low-valence nanosilicon oxide inside. In addition, since it includes each state of SiOx:x<1.0, it can maintain a lower irreversible capacity than general SiO. In addition, since the Si-O bond can suppress the decomposition of the electrolyte, it is possible to reduce the SEI deposited on the surface layer. In addition, since the particle size of the low-valence nanosilicon oxide (particle size obtained by image processing of a cross-sectional TEM image of the low-valence nanosilicon oxide) is 50 nm or less on average, it is easy to form an Si-O bond appropriately. In addition, in the present invention, it is sufficient that the amorphous low-valence nanosilicon oxide is dispersed inside the porous carbon structure, and some of the nanosilicon oxide may have crystallinity.

[0053] That is, the negative electrode active material of the present invention is a Si-Ox having a siloxane bond in the Si phase in order to suppress the decomposition reaction of the electrolyte, which is insufficient in the CVD-Si-C generated from general silane gas. However, since the tetravalent Si constituting SiO becomes an irreversible component, by making the divalent or less SiOx dominant, the irreversible capacity is larger than that of silicon alone, but the irreversible capacity can be maintained lower than that of general SiO. In addition, since the Si-O bond can suppress the decomposition of the electrolyte, it is possible to reduce the SEI deposited on the surface layer of CVD-Si-C. Since the part that mainly contributes to charging and discharging is a low-valent nano-silicon oxide, this material can be defined as CVD-SiOx-C in contrast to CVD-Si-C. In this way, the active material produced can have a high energy density and high-speed charging while maintaining the cycle characteristics of the battery.

[0054] The grain size of the low oxide nanosilicon oxide can be confirmed by TEM-EDX. The conditions for this can be as follows. The negative electrode active material is processed on both cross sections with a focused ion beam processing device (FIB) without being exposed to the atmosphere. The FIB processing device is SIINT's XVision200DB, accelerating voltage 30kV. TEM observation is performed with FEI's TecnaiG2F20, accelerating voltage 200kV, and EDX is EDAX's r-TEM, accelerating voltage 200kV.

[0055] In the present invention, as described above, the low-valence nano silicon oxide preferably has a structure having grains of substantially 50 nm or less and contains a monovalent to divalent oxide compound. The Si-O bond can suppress the decomposition of the electrolyte. In addition, the diffusibility of Li is high, which is suitable for high-speed charging. If the grain size is larger than 50 nm, it is difficult to form Si-O bonds, and for example, only the grain surface layer is oxidized to SiO 2 If the capacitance becomes too high, it will become a resistive component and high-speed charging will no longer be possible.

[0056] A cross-sectional TEM photograph of an example of the negative electrode active material of the present invention is shown in Figure 3. The white parts are low-oxide nanosilicon oxides, and their particle size is 50 nm or less on average.

[0057] When the particle size of the low-oxide nanosilicon oxide becomes large, it becomes difficult to form Si-O bonds. As described later, in the method for producing the negative electrode active material of the present invention, specifically, SiH 4 In the process of decomposing and creating amorphous silicon, it intentionally reacts with oxygen to create Si-O bonds. Therefore, if the particle size is large, the oxygen impregnation is poor, and for example, a concentration distribution of O occurs in the low-valence silicon oxide phase, resulting in SiO 2 In this case, the inside of the phase may become Si, as in the case of CVD-Si-C described above. Furthermore, inside the low-valent nano-silicon oxide grains, there is some zero-valent amorphous Si, and it is desirable for the crystallinity of this to be low. Lowering the crystallinity increases the irreversible capacity, but has the advantage of improving Li acceptance. High crystallinity promotes the electrolyte decomposition reaction specific to Si, resulting in poor cycle characteristics.

[0058] In the negative electrode active material of the present invention, the grain size of zero-valent Si constituting the low-valent nano silicon oxide, calculated by using Scherrer's formula from the peak measured by X-ray diffraction measurement of the negative electrode active material particles, is preferably in the range of 1 nm to 5 nm. Such a grain size of zero-valent Si that is substantially amorphous structure is preferable.

[0059] Calculation of the crystallite size by XRD can be performed, for example, under the following conditions. For broad peaks, analysis can be performed using analysis software TOPAS, for example, under the following conditions. XRD measurement Equipment: Bruker D2 PHASER ·X-ray source:Cu Divergence slit: 0.5° ·Inlet side solar: 4° - Receiving side solar: 4° Calculation of crystallite size Analysis software: DIFFRAC.TOPAS Analysis method: Peak fitting method Emission Profile: CuKa5.lam Function: FP (First Principle) function Refinement Option: Select “Calculate Error” and “Use Extrapolation”

[0060] In addition, in the negative electrode active material of the present invention, the low valence nano silicon oxide is preferably substantially in a composite state of 0 valence, 1 valence, and 2 valence. In this way, the low valence nano silicon oxide is substantially in a composite state of 0 valence, 1 valence, and 2 valence, so that the irreversible capacity can be made lower.

[0061] The negative electrode active material of the present invention has a low-valence nano-silicon oxide phase inside a porous carbon material, and the ratio of silicon to oxygen constituting this low-valence silicon compound is SiO x It is preferable that the ratio is ≦0.7. In addition, the low valence nano silicon oxide is predominantly a monovalent to divalent compound, and the low valence nano silicon oxide phase present inside the porous material may contain a microcrystalline phase of Si with a valence of 0.

[0062] The valence of low-valence nano-silicon oxide can be quantified by NMR (nuclear magnetic resonance) and XPS (X-ray photoelectron spectroscopy).

[0063] NMR measurement can be carried out, for example, under the following conditions. 29 Si MAS NMR (Magic Angle Spinning Nuclear Magnetic Resonance) Equipment: Bruker 700 NMR spectrometer; Probe: 4mm HR-MAS rotor 50μL, -Sample rotation speed: 10kHz, ·Measurement environment temperature: 25℃

[0064] The XPS measurement can be carried out, for example, under the following conditions. XPS ·Equipment: X-ray photoelectron spectrometer, X-ray source: monochromatic Al Kα radiation, X-ray spot diameter: 100μm, Ar ion gun sputtering conditions: 0.5kV 2mm×2mm.

[0065] In the negative electrode active material of the present invention, the negative electrode active material particles are solid 29 It is preferable that hydrogen is not detected near the low valence nano silicon oxide when measured by Si-MAS-NMR. This is because the high valence part is likely to have irreversible capacity if it contains hydrogen as a defect. Solid 29 If the negative electrode active material particles have no hydrogen detected near the low valence nano silicon oxide when measured by Si-MAS-NMR, the irreversible capacity can be further reduced. In the negative electrode active material of the present invention, the low valence portion is considered to have an amorphous structure containing hydrogen.

[0066] FIG. 8 shows a solid-state image of an example of the negative electrode active material of the present invention. 29 Si-MAS-NMR measurement and 29 The results of Si-CP / MAS-NMR measurements are shown below. 29 The Si-MAS-NMR measurement shows a broad peak with a top at around -87 ppm. 29 In the Si-CP / MAS-NMR measurement, the peak width is somewhat narrower, and the region with the highest magnetic field is not detected by the CP / MAS method. This region can be said to be a SiOx structure with no hydrogen (H) atoms in the vicinity (the CP method 1 From H nucleus 29 In order to detect the magnetization of the Si nucleus, 1 No H nuclei 29 (Si nuclei are not detected.) The low wavenumber region is dominated by amorphous Si, but 1 H is present and is detected by the CP / MAS method.

[0067] In addition, in the negative electrode active material of the present invention, the low valence nano silicon oxide is a solid, as shown in FIG. 29In Si-MAS-NMR measurement, it is preferable that the compound has a broad peak with a peak top at about -87 ppm. If the compound has such a peak, it can be more reliably determined that the compound contains SiOx:x<1.0.

[0068] In addition, in the negative electrode active material of the present invention, it is preferable that the low valence nanosilicon oxide dispersed in the porous carbon structure has an x ​​increasing from the center of the porous carbon structure to the surface layer. In the present invention, since the low valence nanosilicon oxide is dispersed in the porous carbon structure, it is likely that the x increases (the composition ratio of oxygen increases) from the center of the porous carbon structure to the surface layer during production. Since the oxidation ratio of silicon is high on the surface, the decomposition of the electrolyte can be more effectively suppressed, while the oxidation ratio of silicon is low inside the active material, so the battery capacity can be increased.

[0069] In addition, in the negative electrode active material of the present invention, it is preferable that the porous carbon structure has at least a carbon-carbon double bond in a part thereof. By having the porous carbon structure have a carbon-carbon double bond, the structure can be made rigid and flexible, and the adverse effect of expansion of the low valence nano silicon oxide inside can be more effectively reduced. Although a commercially available porous carbon structure can be used, it is preferable to select an appropriate porous carbon structure. In the negative electrode active material of the present invention, the porous carbon structure having a carbon-carbon double bond is 13 This can be confirmed by C-MAS-NMR spectrum. Since the structure of the porous carbon is preferably rigid and flexible, it is preferable that it does not contain SiC.

[0070] The negative electrode active material particles preferably have a G / D ratio in the range of 0.85 to 1.15 and a Si / G ratio in the range of 0.25 to 0.5 obtained by Raman spectroscopy. The G / D ratio is the ratio of a G-band peak intensity IG, which is the intensity of a peak derived from a G band, to a D-band peak intensity ID, which is the intensity of a peak derived from a D band, obtained by Raman spectroscopy. The Si / G ratio is the intensity ratio of a Si peak intensity ISi, which is the intensity of a peak derived from a Si band, to a G-band peak intensity IG, which is the intensity of a peak derived from a G band, obtained by Raman spectroscopy.

[0071] If the carbon particles are too hard, they will break when pressed, but if they are too soft, they will break due to the expansion of silicon when it absorbs Li, so there is an optimal range. In addition, if the area of ​​the low-valence silicon oxide part visible on the particle surface is large, the reaction area with the electrolyte is large and it is prone to deterioration relatively quickly, but if it is narrow, the Li acceptance area becomes small and the high-speed charging performance deteriorates. As a guideline showing these, there is an optimal value for the Si / G ratio. That is, if the G / D ratio is within the above range, it is not too hard or too soft. If it is within the above range, it is possible to prevent cracking during pressing or cracking due to volume change when Li is absorbed by low-valence nanosilicon. Also, if the Si / G ratio is within the above range, the area of ​​the low-valence nanosilicon oxide part visible on the particle surface is more appropriate. If it is within the above range, it is possible to ensure high-speed charging while suppressing deterioration.

[0072] <Non-aqueous electrolyte secondary battery negative electrode> Next, the configuration of a negative electrode for a non-aqueous electrolyte secondary battery (hereinafter also referred to as "negative electrode") containing the negative electrode active material of the present invention will be described.

[0073] [Negative electrode composition] Fig. 1 shows a cross-sectional view of a negative electrode including the negative electrode active material of the present invention. As shown in Fig. 1, a negative electrode 10 has a negative electrode active material layer 12 on a negative electrode current collector 11. This negative electrode active material layer 12 may be provided on both sides or only one side of the negative electrode current collector 11. Furthermore, the negative electrode of the nonaqueous electrolyte secondary battery of the present invention does not necessarily need to have the negative electrode current collector 11.

[0074] [Negative electrode current collector] The negative electrode current collector 11 is made of a material having excellent electrical conductivity and excellent mechanical strength. Examples of the conductive material that can be used for the negative electrode current collector 11 include copper (Cu) and nickel (Ni). It is preferable that this conductive material is a material that does not form an intermetallic compound with lithium (Li).

[0075] The negative electrode current collector 11 preferably contains carbon (C) and / or sulfur (S) in addition to the main elements. This is because the physical strength of the negative electrode current collector is improved. In particular, when the current collector has an active material layer that expands during charging, if the current collector contains the above elements, this has the effect of suppressing deformation of the electrode including the current collector. The contents of the above contained elements are not particularly limited, but are preferably 100 mass ppm or less for each. This is because a higher deformation suppression effect can be obtained. Such a deformation suppression effect can further improve cycle characteristics.

[0076] The surface of the negative electrode current collector 11 is preferably roughened, and the ten-point average roughness Rz of the surface is preferably 1.5 μm or more and 5 μm or less. The roughened negative electrode current collector is, for example, a metal foil that has been electrolytically treated, embossed, or chemically etched.

[0077] [Negative electrode active material layer] The negative electrode active material layer 12 may contain a plurality of types of negative electrode active materials such as a carbon-based active material in addition to silicon-based active material particles. Furthermore, in terms of battery design, it may contain other materials such as a thickener (also called a "binding agent" or "binder") and a conductive assistant.

[0078] [Method of manufacturing negative electrode active material and negative electrode] Next, an example of a method for producing the negative electrode active material of the nonaqueous electrolyte secondary battery of the present invention and a negative electrode using the same will be described.

[0079] First, a method for producing the negative electrode active material contained in the negative electrode will be described. The method for producing the negative electrode active material of the present invention is a method for producing a negative electrode active material having negative electrode active material particles, which includes the steps of preparing a porous carbon structure, flowing monosilane gas into the porous carbon structure under heating to deposit silicon inside the porous carbon structure, cooling the material with silicon deposited inside the porous carbon structure to 50°C or less, and introducing oxygen diluted with nitrogen gas into the material with silicon deposited inside the porous carbon structure in a state in which the temperature of the material with silicon deposited inside the porous carbon structure is adjusted to be maintained at 50°C or less after the cooling, thereby changing at least a part of the silicon into low valence nano silicon oxide, which is characterized by producing a negative electrode active material particle in which amorphous low valence nano silicon oxide is dispersed inside the porous carbon structure.

[0080] Each step of the method for producing a negative electrode active material will be described with reference to steps S1 to S4 in FIG.

[0081] First, a porous carbon structure is prepared (step S1). The porous carbon structure prepared here preferably has at least a carbon-carbon double bond in a part thereof. The porous carbon structure prepared here is predominantly of type I in the IUPAC classification, and has a surface area of ​​1400 m2. 2 / g or more, pore volume is 1cm 3 / g or more. By using such IUPAC classification, surface area, and pore volume, silicon can be deposited more efficiently. In addition, the following measurement methods can be used for the IUPAC classification, surface area, and pore volume. Measure the specific surface area / pore distribution using Shimadzu Tristar II Plus by the constant volume method based on the gas adsorption method. The conditions are as follows: Gas used: Nitrogen Environment: Liquid nitrogen Pressure operating range: P / P0 Adsorption 0~0.998 Desorption 0.998~0.10 Pretreatment: Vacuum 200℃ 1 hour

[0082] Next, monosilane gas is caused to flow under heating through the porous carbon structure prepared in step S1, thereby depositing silicon inside the porous carbon structure (step S2).

[0083] After step S1 and before step S2, it is preferable to store the porous carbon structure in a vacuum container and evacuate it. The degree of vacuum can be, for example, about -100 kPa, but is not limited to this. After evacuating, it is preferable to restore the pressure with nitrogen and heat to about 350 to 450°C using an external heater while nitrogen is flowing. This heating can be performed for 5 minutes to 1 hour. By performing such evacuation and preheating in the presence of nitrogen, nucleation for silicon deposition in step S2 and removal of hydrogen and water attached to the porous carbon structure can be performed, so that silicon deposition in step S2 can be performed more reliably.

[0084] The silicon deposition in step S2 can be performed by flowing monosilane gas at, for example, about 400° C. to 500° C. The deposition time can be, for example, 30 minutes to 10 hours.

[0085] Next, the material with silicon deposited inside the porous carbon structure is cooled to 50° C. or less (step S3). In this step, it is preferable to cool the material while flowing nitrogen gas. In this cooling, the material can be cooled to room temperature, for example.

[0086] After the cooling (step S3), the temperature of the material with silicon deposited inside the porous carbon structure is adjusted to be kept below 50°C, and oxygen diluted with nitrogen gas is introduced into the material with silicon deposited inside the porous carbon structure to convert at least a part of the silicon into low-valence nanosilicon oxide (step S4). This step allows the formation of Si-O bonds. It is more preferable to maintain the temperature at 35°C or less.

[0087] The dilution of oxygen with nitrogen can be, for example, 5 to 50 times, and preferably 10 to 30 times. This dilution degree can typically be 20 times.

[0088] Furthermore, in this step S4, if the internal temperature rises and exceeds 50° C., silicon dioxide will be generated in some parts, which is not preferable as a negative electrode active material. Therefore, in this step S4, it is necessary to adjust the temperature of the material to be maintained at 50° C. or less. In addition, the material temperature in step S4 is preferably set to, for example, 25° C. or more, and more preferably 30° C. or more, in order to facilitate the oxidation reaction and facilitate the generation of Si-O bonds.

[0089] The oxidation time in step S4 (flow time of oxygen diluted with nitrogen gas) can be, for example, 30 minutes to 5 hours, preferably 1 hour to 3 hours. After the flow of oxygen diluted with nitrogen gas, the flow can be switched to nitrogen gas for further cooling. The flow of only nitrogen gas can be, for example, 30 minutes to 2 hours.

[0090] In the oxidation by the flow of oxygen diluted with nitrogen gas, it is preferable to adjust the low valence nano silicon oxide dispersed in the porous carbon structure so that x increases from the center of the porous carbon structure to the surface layer. In the porous carbon structure, the cross-sectional area of ​​the pore structure tends to be large at the particle surface and to become smaller toward the inside of the particle. Therefore, by performing oxidation by the flow of oxygen diluted with nitrogen gas as in the present invention, x naturally tends to increase from the center of the porous carbon structure to the surface layer.

[0091] The material is then removed from the storage vessel. Through the above steps, negative electrode active material particles can be produced in which amorphous low-valent nanosilicon oxide is dispersed inside the porous carbon structure.

[0092] When producing the negative electrode active material produced in this manner, it is preferable to adjust the amount of silicon deposition and the degree of oxidation so that the proportion of the porous carbon structure in the entire negative electrode active material particles is 38 mass% or more and 63 mass% or less.

[0093] <Lithium-ion secondary battery> Next, as a specific example of a nonaqueous electrolyte secondary battery using the above-mentioned negative electrode active material of the present invention, a laminate film type lithium ion secondary battery will be described.

[0094] [Configuration of laminated film type secondary battery] The laminated film type lithium ion secondary battery 30 shown in FIG. 2 is a battery in which a wound electrode body 31 is housed inside a sheet-like exterior member 35. This wound electrode body 31 has a separator between the positive electrode and the negative electrode, and is wound. There are also cases where a separator is between the positive electrode and the negative electrode and a laminate is housed. In either electrode body, a positive electrode lead 32 is attached to the positive electrode, and a negative electrode lead 33 is attached to the negative electrode. The outermost periphery of the electrode body is protected by a protective tape.

[0095] The positive and negative electrode leads 32, 33 are led out in one direction, for example, from the inside to the outside of the exterior member 35. The positive electrode lead 32 is formed of a conductive material such as aluminum, and the negative electrode lead 33 is formed of a conductive material such as nickel or copper.

[0096] The exterior member 35 is, for example, a laminate film in which a fusion layer, a metal layer, and a surface protection layer are laminated in this order, and the outer peripheral edges of the fusion layers of the two films of this laminate film are fused together or pasted together with an adhesive so that the fusion layer faces the electrode body 31. The fusion part is, for example, a film such as polyethylene or polypropylene, and the metal part is aluminum foil, etc. The protection layer is, for example, nylon, etc.

[0097] An adhesive film 34 is inserted between the exterior member 35 and the positive and negative electrode leads to prevent outside air from entering. The material for this is, for example, polyethylene, polypropylene, or polyolefin resin.

[0098] The positive electrode has a positive electrode active material layer on either or both sides of a positive electrode current collector, similar to the negative electrode 10 in FIG.

[0099] The positive electrode current collector is made of a conductive material such as aluminum.

[0100] The positive electrode active material layer contains one or more positive electrode materials capable of absorbing and releasing lithium ions, and may contain other materials such as a positive electrode binder, a positive electrode conductive assistant, a dispersant, etc., depending on the design. In this case, details regarding the positive electrode binder and the positive electrode conductive assistant are the same as, for example, the negative electrode binder and the negative electrode conductive assistant already described.

[0101] The positive electrode material is preferably a lithium-containing compound. Examples of the lithium-containing compound include a composite oxide made of lithium and a transition metal element, or a phosphate compound containing lithium and a transition metal element. Among these positive electrode materials, compounds containing at least one of nickel, iron, manganese, and cobalt are preferred. Examples of the chemical formula of these compounds include Lix M 1 O 2 or Li y M 2 PO 4 is represented by. In the formula, M 1 , M 2 represents at least one or more transition metal elements. The values of x and y are different depending on the charge and discharge state of the battery, but are generally represented by 0.05 ≦ x ≦ 1.10 and 0.05 ≦ y ≦ 1.10.

[0102] Examples of the composite oxide having lithium and a transition metal element include lithium cobalt composite oxide (Li x CoO 2 ), lithium nickel composite oxide (Li x NiO 2 ), and lithium nickel cobalt composite oxide. Examples of the lithium nickel cobalt composite oxide include lithium nickel cobalt aluminum composite oxide (NCA) and lithium nickel cobalt manganese composite oxide (NCM).

[0103] Examples of the phosphate compound having lithium and a transition metal element include lithium iron phosphate compound (LiFePO 4 ) or lithium iron manganese phosphate compound (LiFe 1-u Mn u PO 4 (0 < u < 1)) and the like. By using these positive electrode materials, a high battery capacity can be obtained, and excellent cycle characteristics can also be obtained.

[0104] [Negative electrode] The negative electrode has the same configuration as the negative electrode 10 for a lithium ion secondary battery shown in FIG. 1 described above. For example, a negative electrode active material layer is provided on both sides of the current collector. It is preferable that the negative electrode charging capacity is larger than the electric capacity obtained from the positive electrode active material agent (charging capacity as a battery). Thereby, precipitation of lithium metal on the negative electrode can be suppressed.

[0105] The positive electrode active material layer is provided on a part of both sides of the positive electrode current collector, and similarly, the negative electrode active material layer is provided on a part of both sides of the negative electrode current collector. In this case, for example, the negative electrode active material layer provided on the negative electrode current collector has a region where the opposing positive electrode active material layer is not present. This is for the purpose of designing a stable battery.

[0106] The region where the negative electrode active material layer and the positive electrode active material layer do not face each other is hardly affected by charging and discharging, so the state of the negative electrode active material layer is maintained as it is immediately after formation, and the composition of the negative electrode active material can be accurately examined with good reproducibility regardless of the presence or absence of charging and discharging.

[0107] [Separator] The separator separates the positive electrode from the negative electrode, prevents current short circuit caused by contact between the electrodes, and allows lithium ions to pass through. The separator is formed of a porous film made of, for example, synthetic resin or ceramic, and may have a laminated structure in which two or more types of porous films are laminated. Examples of synthetic resins include polytetrafluoroethylene, polypropylene, and polyethylene.

[0108] [Electrolyte] At least a portion of the active material layer or the separator is impregnated with a liquid electrolyte (electrolytic solution). This electrolytic solution contains an electrolyte salt dissolved in a solvent, and may contain other materials such as additives.

[0109] The solvent may be, for example, a non-aqueous solvent. Examples of the non-aqueous solvent include ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, 1,2-dimethoxyethane, or tetrahydrofuran. Among these, it is desirable to use at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. This is because better characteristics can be obtained. In this case, more advantageous characteristics can be obtained by combining a high-viscosity solvent such as ethylene carbonate or propylene carbonate with a low-viscosity solvent such as dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. This is because the dissociation property and ion mobility of the electrolyte salt are improved.

[0110] When an alloy-based negative electrode is used, it is particularly desirable that the solvent contains at least one of halogenated chain carbonates or halogenated cyclic carbonates. This allows a stable coating to be formed on the surface of the negative electrode active material during charging and discharging, particularly during charging. Here, the halogenated chain carbonate is a chain carbonate having a halogen as a constituent element (at least one hydrogen is substituted with a halogen). Also, the halogenated cyclic carbonate is a cyclic carbonate having a halogen as a constituent element (i.e., at least one hydrogen is substituted with a halogen).

[0111] The type of halogen is not particularly limited, but fluorine is preferred because it forms a better coating than other halogens. Also, the more halogens there are, the more desirable they are because the resulting coating is more stable and the decomposition reaction of the electrolyte is reduced.

[0112] Examples of halogenated chain carbonates include fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, etc. Examples of halogenated cyclic carbonates include 4-fluoro-1,3-dioxolan-2-one, 4,5-difluoro-1,3-dioxolan-2-one, etc.

[0113] It is preferable that the solvent additive contains an unsaturated carbon-bonded cyclic carbonate. This is because a stable coating is formed on the negative electrode surface during charging and discharging, and the decomposition reaction of the electrolyte can be suppressed. Examples of the unsaturated carbon-bonded cyclic carbonate include vinylene carbonate and vinylethylene carbonate.

[0114] It is also preferable that the solvent additive contains sultone (cyclic sulfonic acid ester), because this improves the chemical stability of the battery. Examples of sultones include propane sultone and propene sultone.

[0115] Furthermore, it is preferable that the solvent contains an acid anhydride, because this improves the chemical stability of the electrolyte. As the acid anhydride, for example, propane disulfonic acid anhydride can be mentioned.

[0116] The electrolyte salt may include at least one of light metal salts such as a lithium salt. Examples of the lithium salt include lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) etc.

[0117] The content of the electrolyte salt is preferably 0.5 mol / kg or more and 2.5 mol / kg or less relative to the solvent, because high ionic conductivity can be obtained. EXAMPLES

[0118] The present invention will be described in more detail below by showing examples and comparative examples of the present invention, but the present invention is not limited to these examples.

[0119] Example 1 A negative electrode active material was prepared according to the following procedure, and further, a laminate film type lithium ion secondary battery 30 shown in FIG. 2 was fabricated.

[0120] The negative electrode active material was produced as follows. First, a surface area (BET specific surface area) of 2483 m 2 / g, pore volume 1.35 cm3 A porous carbon material (porous carbon structure) having a particle diameter (D50) of 11 μm and an IUPAC classification type I was prepared. This porous carbon material was stored in a vacuum container and evacuated to -90 kPa. Next, the pressure was restored with nitrogen, and the material was heated to 400 ° C. using an external heater while nitrogen was flowing. After 30 minutes of heating, the temperature was raised to 415 ° C., monosilane gas was flowed, and deposition was performed for 4 hours. Then, the material was cooled to room temperature while nitrogen gas was flowing. After lowering the temperature to 25 ° C., oxygen diluted 20 times with nitrogen was introduced, and the material temperature was adjusted to 50 ° C. or less to form Si-O bonds. Next, nitrogen containing oxygen was flowed for 2 hours, and when the material temperature became 30 ° C. or less, it was switched to nitrogen gas, and after flowing for 60 minutes, the material was taken out of the storage container and used as a negative electrode active material.

[0121] [Measurement of negative electrode active material] The negative electrode active material prepared as described above was subjected to TEM-EDX, XRD analysis, NMR analysis, and Raman spectroscopic analysis.

[0122] [Preparation of negative electrode] The negative electrode active material (active material containing CVD-SiOx-C) prepared as described above, graphite, conductive additive 1 (carbon nanotubes, CNT), conductive additive 2 (carbon particles having a median diameter of approximately 50 nm), sodium polyacrylate, and carboxymethyl cellulose (hereinafter referred to as CMC) were mixed in a dry mass ratio of 9.3:83.7:1:1:4:1, and then diluted with pure water to form a negative electrode mixture slurry.

[0123] In addition, an electrolytic copper foil having a thickness of 15 μm was used as the negative electrode current collector. This electrolytic copper foil contained carbon and sulfur at a concentration of 70 mass ppm each. Finally, the negative electrode mixture slurry was applied to the negative electrode current collector and dried at 100° C. for 1 hour in a vacuum atmosphere. After drying, the deposition amount of the negative electrode active material layer per unit area on one side of the negative electrode (also called the area density) was 7.0 mg / cm 2 It was.

[0124] [Assembling a coin battery for testing] Next, the solvents ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed, and then the electrolyte salt (lithium hexafluorophosphate: LiPF 6 ) was dissolved to prepare an electrolyte solution. In this case, the solvent composition was EC:DMC=30:70 in volume ratio, and the content of the electrolyte salt was 1 mol / kg relative to the solvent. As additives, vinylene carbonate (VC) and fluoroethylene carbonate (FEC) were added in amounts of 1.0 mass% and 2.0 mass%, respectively.

[0125] Next, a coin battery was assembled as follows: First, a 1 mm thick Li foil was punched out to a diameter of 16 mm and attached to an aluminum clad.

[0126] Next, the negative electrode obtained above was punched out to a diameter of 15 mm, and this was placed opposite a Li foil attached to an aluminum clad via a separator. After injection of an electrolyte, a 2032 coin battery was produced.

[0127] [Measurement of initial efficiency] The initial efficiency was measured under the following conditions. First, the coin battery for the initial efficiency test was charged (initial charge) in CCCV mode with a charge rate equivalent to 0.03C. CV was 0V and the end current was 0.04mA. Next, CC discharge (initial discharge) was performed with a discharge rate of 0.03C and an end voltage of discharge of 1.2V.

[0128] When investigating the initial charge / discharge characteristics, the initial efficiency (hereinafter sometimes referred to as initial efficiency) was calculated using the formula: initial efficiency (%) = (initial discharge capacity / initial charge capacity) x 100.

[0129] [Production and evaluation of lithium-ion secondary batteries] From the initial data obtained, the counter positive electrode was designed so that the utilization rate of the negative electrode would be 95%. The utilization rate was calculated from the capacity of the positive and negative electrodes obtained with the counter electrode Li according to the following formula. Utilization rate = (positive electrode capacity - negative electrode loss) / (negative electrode capacity - negative electrode loss) x 100 Based on this design, lithium ion secondary batteries (lithium ion secondary batteries as shown in FIG. 2) of the examples and comparative examples were manufactured. Battery evaluation was carried out for each of the lithium ion secondary batteries of the examples and comparative examples.

[0130] The cycle characteristics were investigated as follows. First, in order to stabilize the battery, two cycles of charge and discharge were performed at 0.2C in an atmosphere of 25°C, and the discharge capacity of the second cycle was measured. The battery cycle characteristics were calculated from the discharge capacity of the third cycle, and the battery test was stopped after 1000 cycles. Charge and discharge were performed at 0.7C and 0.5C. The charge voltage was 4.3V, the discharge end voltage was 2.5V, and the charge end rate was 0.07C.

[0131] The results of each measurement are shown in Table 1. Table 1 also shows Comparative Examples 1 to 3 and Examples 2 to 17, which will be described later.

[0132] [Table 1]

[0133] Comparative Example 1 A porous carbon structure similar to that in Example 1 was prepared. Then, SiH 4 Using gas, amorphous silicon was formed from the surface layer of the porous carbon structure particle to a portion close to the center at 415°C. Since Si-H bonds are included in this state, the temperature was raised to 435°C to stabilize the Si-Si. After that, it was cooled to room temperature and the sample was taken out in the atmosphere. By using this method, it is possible to prototype a material that does not contain low-valence silicon oxide compounds (unlike the present invention). Various measurements were performed in the same manner as in Example 1 and are shown in Table 1. The capacity and initial coulombic efficiency were high, but the reactivity with the electrolyte was high, and the battery cycle characteristics deteriorated, especially the high-speed charging performance was Li deposition.

[0134] Comparative Example 2 A negative electrode active material was produced in the same manner as in Example 1, except that the SiOx phase was enlarged by decomposing the same gas as in Comparative Example 1 at 435°C. Various measurements were performed in the same manner as in Example 1, and are shown in Table 1. According to the analysis of the cross-sectional TEM image, the particle size of the low-valence nanosilicon oxide was 55 nm. The SiOx phase also contained Si 0-valence, and the probability of them coming into contact with the electrolyte increased, and the battery characteristics deteriorated.

[0135] Comparative Example 3 Amorphous silicon was formed and cooled in the same manner as in Comparative Example 1, and then dry air was introduced, and the material temperature rose to 55° C. Various measurements were performed in the same manner as in Example 1, and the results are shown in Table 1. In particular, Li acceptance deteriorated, and Li precipitated during high-speed charging.

[0136] (Examples 2 to 11) A negative electrode active material was produced in the same manner as in Example 1, except that a porous carbon structure having different properties was used as the first prepared porous carbon structure, as shown in Table 1. In addition, an evaluation was performed in the same manner as in Example 1. From the results of Examples 2 to 11, when considering the balance between capacity, efficiency, etc., it was found that the pore volume of 1 cm 3 / g or more, BET specific surface area 1400m 2 / g or more, IUPAC classification of type I is considered preferable.

[0137] (Examples 12 to 16) A negative electrode active material was produced using the same porous carbon structure as in Example 1, but with the following conditions: First, the temperature was raised to 415°C, monosilane gas was introduced, and deposition was carried out for 4 hours. Then, the temperature was raised to 415°C, and Si 0+ The grain size was grown. Various measurements were performed in the same manner as in Example 1, and the results are shown in Table 1. As a result, the closer the structure was to an amorphous structure, the lower the capacity was, but the high-speed charging property and the battery cycle characteristics were improved. From the results of Examples 12 to 16, the closer the structure was to an amorphous structure, the lower the capacity was, but the high-speed charging property and the battery cycle characteristics were improved.

[0138] (Example 17) A negative electrode active material was produced by carrying out an oxidation treatment on a porous carbon structure similar to that of Example 1 using diluted oxygen at half the amount used in Example 1. Various measurements were carried out in the same manner as in Example 1, and the results are shown in Table 1. As a result, defects were generated in the SiOx region.

[0139] [Explanation of each figure] FIG. 5 shows the solid-state negative electrode active material of Example 1 and the solid-state active materials of each control. 29 The results of Si-MAS-NMR measurements are shown. As control examples, the results of NMR measurements of amorphous silicon itself, SiOx particles coated with carbon (SiO-C), and SiO-C made from silicone heat-treated at 1000°C under argon are shown. The negative electrode active material of Example 1 has an amorphous silicon peak and is shown to have a large SiOx region.

[0140] Fig. 6 shows the change in the depth direction measurement of the O1s region in the XPS measurement of the negative electrode active material in Example 1. As can be seen from Fig. 6, the O1s peak decreases in the depth direction from the surface, and the oxygen concentration decreases from the surface toward the deeper layer.

[0141] FIG. 7 shows a graph illustrating the results of the Si2p region in the XPS measurements of the negative electrode active materials in Example 1, Comparative Example 1, and Comparative Example 3. In Example 1, a peak is observed at 99 to 100 eV, indicating that there is a large amount of low-valence nanosilicon oxide (SiOx) components. In Comparative Example 1, a peak is observed at 98.5 eV, indicating that there is a large amount of Si components. In Comparative Example 3, in addition to the peaks at 99 to 100 eV, a shoulder peak is observed at 103 eV, indicating that there is a large amount of SiO 2 It is clear that it contains many ingredients.

[0142] FIG. 9 shows the results of Example 1 and a control example in which SiO-C made from silicone was heat-treated at 1000° C. under argon. 13 The C-MAS-NMR spectrum is shown. In Example 1, a peak due to the carbon-carbon double bond is observed, and also a peak due to the spinning side band of the carbon-carbon double bond is observed.

[0143] Figure 10 shows the results of TEM-EDX measurement of the negative electrode active material of Example 1. The upper figure is a cross-sectional TEM photograph, and the straight lines indicate the measurement points. The lower figure is a graph showing the relationship between the distance from the surface (on the straight line in the upper figure) and the mass % of the element. As can be seen from Figure 10, the oxygen concentration decreases from the surface of the negative electrode active material particles toward the deeper layers.

[0144] 11 shows the X-ray diffraction spectra of Examples 1, 2, 15, and 16. All of these show a peak near 2θ=28°, and the silicon crystallite size was calculated from this peak. The same is true for the other Examples and Comparative Examples.

[0145] Fig. 12 shows a graph illustrating the charge / discharge characteristics of Example 1, Comparative Example 1, and Example 11. Fig. 13 is a partially enlarged view of Fig. 12. As shown in Figs. 12 and 13, Comparative Example 1 shows the presence of crystalline Si, whereas Example 1 suggests the presence of SiOx.

[0146] The present specification includes the following aspects. [1]: A negative electrode active material having negative electrode active material particles, The negative electrode active material particles include a porous carbon structure, Amorphous low-valence nanosilicon oxide is dispersed inside the porous carbon structure, The low valence nano silicon oxide includes each state of SiOx:x<1.0, The low-valence nanosilicon oxide is a negative electrode active material characterized in that its particle size, as determined by image processing of a cross-sectional TEM image, is 50 nm or less on average. [2]: The negative electrode active material according to [1] above, wherein the low-valent nanosilicon oxide is substantially in a composite state of zero valence, monovalence, and divalence. [3]: The negative electrode active material particles are solidified. 29 The negative electrode active material according to the above [1] or [2], in which no hydrogen is detected in the vicinity of the low valence nanosilicon oxide when measured by Si-MAS-NMR. [4]: The negative electrode active material according to any one of [1] to [3] above, wherein the low-valent nanosilicon oxide dispersed in the porous carbon structure has x increasing from the center of the porous carbon structure toward the surface layer. [5]: The negative electrode active material according to any one of [1] to [4] above, wherein the porous carbon structure has a carbon-carbon double bond in at least a part thereof. [6]: The negative electrode active material according to any one of [1] to [5] above, wherein the proportion of the porous carbon structure in the entire negative electrode active material particles is 38 mass % or more and 63 mass % or less. [7]: The low valence nano silicon oxide is a solid 29 The negative electrode active material according to any one of [1] to [6] above, which has a broad peak with a top at about -87 ppm in Si-MAS-NMR measurement. [8]: The negative electrode active material according to any one of [1] to [7] above, wherein the grain size of zero-valent Si constituting the low-valent nanosilicon oxide, calculated using the Scherrer equation from a peak measured by X-ray diffraction measurement of the negative electrode active material particles, is in the range of 1 nm to 5 nm. [9]: The negative electrode active material according to any one of [1] to [8], wherein the negative electrode active material particles have a G / D ratio in the range of 0.85 to 1.15 as determined by Raman spectroscopy, and a Si / G ratio of 0.25 or more and 0.5 or less.

[10] : The porous carbon structure is predominantly type I in the IUPAC classification and has a surface area of ​​1400 m 2 / g or more, pore volume is 1cm 3 / g or more of the negative electrode active material according to any one of [1] to [9] above.

[11] : A method for producing a negative electrode active material having negative electrode active material particles, comprising: Providing a porous carbon structure; depositing silicon inside the porous carbon structure by flowing monosilane gas through the porous carbon structure under heating; cooling the material with silicon deposited inside the porous carbon structure to below 50°C; After the cooling, while adjusting the temperature of the material in which silicon is deposited inside the porous carbon structure to be kept at 50° C. or less, oxygen diluted with nitrogen gas is introduced into the material in which silicon is deposited inside the porous carbon structure, thereby converting at least a part of the silicon into low-valence nanosilicon oxide. and thereby producing negative electrode active material particles having amorphous low valence nano silicon oxide dispersed inside the porous carbon structure.

[0147] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]

[0148] 10...Negative electrode, 11...Negative electrode current collector, 12...Negative electrode active material layer, 30...Lithium ion secondary battery (laminate film type), 31...electrode body, 32...Positive electrode lead (positive electrode aluminum lead), 33...Negative electrode lead (negative electrode nickel lead), 34...adhesive film, 35...exterior part.

Claims

1. A negative electrode active material having negative electrode active material particles, The negative electrode active material particles include a porous carbon structure, Amorphous low-valence nanosilicon oxide is dispersed inside the porous carbon structure, The low valence nano silicon oxide includes each state of SiOx: x < 1.0, The low-valence nanosilicon oxide has an average particle size of 50 nm or less as determined by image processing of a cross-sectional TEM image.

2. The negative electrode active material according to claim 1 , wherein the low-valent nano-silicon oxide is substantially in a composite state of zero valence, monovalence and divalence.

3. The negative electrode active material particles are solidified 29 2. The negative electrode active material according to claim 1, wherein when measured by Si-MAS-NMR, hydrogen is not detected in the vicinity of the low valence nanosilicon oxide.

4. The negative electrode active material according to claim 1, characterized in that the low valence nanosilicon oxide dispersed in the porous carbon structure has x increasing from the center of the porous carbon structure to the surface layer.

5. 2. The negative electrode active material according to claim 1, wherein the porous carbon structure has a carbon-carbon double bond at least in a part thereof.

6. 2 . The negative electrode active material according to claim 1 , wherein the proportion of the porous carbon structure in the entire negative electrode active material particles is 38% by mass or more and 63% by mass or less.

7. The low valence nano silicon oxide is a solid 29 2. The negative electrode active material according to claim 1, which has a broad peak with a top at about −87 ppm in Si-MAS-NMR measurement.

8. The grain size of zero-valent Si constituting the low-valent nanosilicon oxide calculated using the Scherrer formula from the peak measured by X-ray diffraction measurement of the negative electrode active material particles is in the range of 1 nm to 5 nm. The negative electrode active material according to claim 1.

9. The negative electrode active material according to claim 1, characterized in that the negative electrode active material particles have a G / D ratio obtained by Raman spectroscopy in the range of 0.85 to 1.15 and a Si / G ratio of 0.25 or more and 0.5 or less.

10. The porous carbon structure is predominantly Type I in the IUPAC classification and has a surface area of ​​1400 m 2 / g or more, pore volume is 1 cm 3 2. The negative electrode active material according to claim 1, wherein the molecular weight of the negative electrode active material is 1 / g or more.

11. A method for producing a negative electrode active material having negative electrode active material particles, comprising: Providing a porous carbon structure; depositing silicon inside the porous carbon structure by flowing monosilane gas through the porous carbon structure under heating; Cooling the material with silicon deposited inside the porous carbon structure to below 50° C.; After the cooling, while adjusting the temperature of the material in which silicon is deposited inside the porous carbon structure to be kept at 50° C. or less, oxygen diluted with nitrogen gas is introduced into the material in which silicon is deposited inside the porous carbon structure, thereby converting at least a part of the silicon into low-valence nano-silicon oxide. and thereby producing negative electrode active material particles having amorphous low valence nano silicon oxide dispersed inside the porous carbon structure.

Citation Information

Patent Citations

  • Nanometer silicon-oxygen-carbon structure composite material, preparation method thereof, negative electrode and electrochemical device

    CN116190581A

  • Novel material having highly durable lithium insertion and method for manufacturing the same

    JP2018534720A

  • Decomposition of silicon-containing precursors onto porous scaffolds

    JP2020514231A

  • Silicon-carbon composite materials and methods

    JP2022547660A

  • Nonaqueous electrolytic secondary battery and its manufacture

    JP1994325765A